RNAi and viral heart infections - Kurreck, Jens (Henry Stewart Talks, 2007)
Coxsackievirus B3, Design of efficient antiviral siRNAs, Plaque reduction assays, Virus escape, siRNA double expression vectors (SiDEx), Strand selectivity of virus silencing, Silencing of the host receptor (Coxsackievirus-adenovirus receptor)
Archived at 2016/04/17